THE PAST, PRESENT, AND FUTURE OF DENTISTRY THROUGH LENSES: A SHORT COMMUNICATION - MUKHERJEE, SUMAN; DASGUPTA, SHARMISTHA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
This article gives a contemplative viewpoint on the lenses in dentistry.